Figs 26–31 in Coccolithophorids in Polar Waters: Wigwamma spp. Revisited ... - Thomsen, Helge A.; Østergaard and Mikal Heldal, Jette B. (Zenodo, 2013)
Figs 26–31. Wigwamma antarctica TEM (Figs 26–30) and LM (Fig. 31) whole mounts (Antarctica / EPOS). 26 – complete cell with coiled up haptonema; 27 – complete cell; notice that the entire cell almost equals an Emiliana huxleyi coccolith in overall size; 28 – detail from Fig. 26 showing the two basic types of coccoliths; 29 – detail of flagellar pole coccolith; notice the protruding finger-like projection of one rod, the notched interlocking between a rod and the subtending enlarged crystallite; 30 – reversed printing of body coccolith showing scale rim calcification and base plate patterning (radial fibres); 31 – light micrograph (Nomarski contrast) of whole cell. ... : Published as part of Thomsen, Helge A. & Østergaard and Mikal Heldal, Jette B., 2013, Coccolithophorids in Polar Waters: Wigwamma spp. Revisited, pp. 237-256 in Acta Protozoologica 52 on page 248, DOI: 10.4467/16890027AP.14.007.1444, http://zenodo.org/record/13193273 ...